2005
DOI: 10.1044/1092-4388(2005/049)
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Computer-Based Intervention Through Acoustically Modified Speech (Fast ForWord) in Severe Mixed Receptive—Expressive Language Impairment

Abstract: Seventy-seven children between the ages of 6 and 10 years, with severe mixed receptive-expressive specific language impairment (SLI), participated in a randomized controlled trial (RCT) of Fast ForWord (FFW; Scientific Learning Corporation, 1997, 2001). FFW is a computer-based intervention for treating SLI using acoustically enhanced speech stimuli. These stimuli are modified to exaggerate their time and intensity properties as part of an adaptive training process. All children who participated in the RCT main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
0
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(118 citation statements)
references
References 46 publications
8
99
0
11
Order By: Relevance
“…Although Troia and Whitney's 31 study reported significant improvement in expressive language and greater gain in phonological awareness skills (limited to blending task) in the training group than in the untrained comparison group, neither group showed improvement in reading skills. 23,31 To summarize, in six of the eight independent studies that have reported improvement in the language skills of children after FFW intervention, the findings are probably a result of test-retest or maturational effects; [22][23][24][25][26][27]29,30 only two studies reported improvements in the language skills of children with SLI and in poor academic achievers. 28,31 One study found no significant improvement in the language measure at all.…”
Section: Discussion Fast Forword or Fast Forword-languagementioning
confidence: 99%
See 1 more Smart Citation
“…Although Troia and Whitney's 31 study reported significant improvement in expressive language and greater gain in phonological awareness skills (limited to blending task) in the training group than in the untrained comparison group, neither group showed improvement in reading skills. 23,31 To summarize, in six of the eight independent studies that have reported improvement in the language skills of children after FFW intervention, the findings are probably a result of test-retest or maturational effects; [22][23][24][25][26][27]29,30 only two studies reported improvements in the language skills of children with SLI and in poor academic achievers. 28,31 One study found no significant improvement in the language measure at all.…”
Section: Discussion Fast Forword or Fast Forword-languagementioning
confidence: 99%
“…Stevens et al 28 reported improvement in the receptive language skills of eight children with SLI and of 12 children with typically developing language after FFW training, but not in a typically developing untrained comparison group. Two independent randomized controlled trials by Cohen et al 29 and Gillam et al 30 compared the effectiveness of FFW-L and other intervention programmes and found no significant between-group differences in the gains made in the language measure after training, apart from in the phonological awareness skills. Cohen et al 31 reported that the FFW-L group slightly outperformed the others, whereas Gillam et al 32 reported that the FFW-L group and the computer-assisted language intervention group performed equally well in phonological awareness tests.…”
Section: Discussion Fast Forword or Fast Forword-languagementioning
confidence: 99%
“…However, these studies typically required the intervention of a suitably trained clinician, which limited their practical application. In contrast, athome personal computer (PC)-based perceptual training has received much recent attention as a possible treatment for central auditory processing disorder and dyslexia [45][46][47][48][49][50]. Although the mechanism by which PCbased training enhances performance in these disorders is not well understood [51], training effects can be substantial.…”
Section: Perceptual Training Of Hearing Aid Usersmentioning
confidence: 99%
“…The programs vary in how far they were intended to be used independently of an SLP and in whether or not they are effective when compared to tabletop interventions with populations of language impaired children (Cohen et al, 2005;Gillam, Crofford, Gale, & Hoffman, 2001;Hook, Macaruso & Jones, 2001;Troia & Whitney, 2003).…”
Section: Using Computers In Speech and Language Therapymentioning
confidence: 99%